AN EPIDEMIOLOGICAL STUDY ON FOOT AND MOUTH DISEASE OUTBREAK IN CATTLE OF ERODE DISTRICT OF TAMILNADU - P. Shamsudeen; R. Yasothai; T.R. Gopalakrishna Murthy (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Foot and Mouth Disease (FMD) is one of the most important viral diseases of livestock especially cattle causing heavy economic losses to farmers. FMD outbreak in cattle during the period from 2002 to 2008 in Erode District of Tamil Nadu is reported. The incidence of FMD in cattle and buffaloes, season, morbidity and mortality were investigated. The results revealed that the disease generally occurred from August to February of the calendar year with very high prevalence from November to February. The disease caused an average mortality of 16.1 per cent in cattle, with highest mortality rate of 32.6 per cent during 2003-04, followed by 16 per cent mortality in 2007-08, 4.2 per cent in 2002-03 and a lowest mortality rate of 2.5 per cent during 2004-05. In  2007-08, a  total  of  2352  cattle and buffalo  were  affected  with a mortality of 16 per cent among morbid animals. The disease affected 1578 cows, 349 calves, 349 buffaloes and 76 buffalo calves with a mortality percentage of 14.3, 29.8, 10.6 and 13.2 respectively. The disease caused 17.1 per cent mortality in white cattle and 11.1 per cent mortality in buffaloes. Among morbid animals, the mortality in adults (cow and buffalo) and young ones (calves and buffalo calves) were 13.7 per cent and 26.8 per cent, respectively. Higher morbidity and mortality were observed in areas irrigated with Lower Bhavani Project (LBP) Channel and Cauvery river water irrigation than dry land area of the district.